Performance of organic and inorganic substances as inhibitors for chloride-induced corrosion in concrete - Aydin, Ozlem; Cizmeciglu, Zeki (CARL HANSER VERLAG, 2015)
Studies have been carried out to investigate the concrete corrosion inhibitor performance of silica fume admixture and an admixture of amino alcohols containing organic and inorganic substances. The concrete specimens with and without admixtures were subjected to accelerated corrosion tests to determine the time to corrosion initiation. The results showed that the specimens admixtured with nitrogen containing organic and inorganic inhibitors performed slightly better than concrete specimens with silica fume admixture.
Keywords: Reinforcement; inhibitor; corrosion; concrete; chloride; PHYSICAL-PROPERTIES; STEEL; Materials Science